THE EFFECT OF HEALTH CADRE MOTIVATION ON PERFORMANCE IN EFFORTS TO IMPROVE TODDLER GROWTH: METAANALYSIS - Rahmawati A, Anita; Akhyar, Muhammad; Setyowati B, Retno; Mulyani B, Sri (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Health cadres are the spearhead in implementing health programs at the village level. In the context of toddler growth, cadre duties include monitoring child growth and development and early detection of toddler health problems. Cadre motivation is seen as a factor that influences how much involvement and dedication cadres have in carrying out their duties well. Objective : This article aims to analyze the influence of health cadre motivation on performance in efforts to improve toddler growth. Research Methods/ Implementation Methods : This study is a meta-analysis using the PRISMA flowchart and PICO model. Population: toddler health cadres. Intervention: have good motivation. Comparison: poor motivation, Outcome: Cadre performance. The process of searching for articles by searching through databases in Google scholar, Scopus, ProQuest, PubMed, Elsevier, and Science direct. The keywords used are